Either she dosent want to admit that she likes you or she dosnt even like u
Answer:
well, she may have her walls up when you are around her. she is scared to hurt you so she just pushes you away instead. My suggestion would be to act like her friend and that every time you work your way closer pretend that its just like in the beginning aka keep pretending your just regular friends nothing more. Then when you notice her starting to open up a little more start working your way out of the friend zone.
Step-by-step explanation:
Answer:
0.0238
Step-by-step explanation:
Total number of persons to be chosen from = 7
If each person has an equal probability of being selected ;
Number of persons to be selected = 2
Probability = required outcome / Total possible outcomes
P(Anna first) = 1 / 7
Recall; this is a selection without replacement ;
P(Darlene second) = 1 / 6
1/7 * 1/ 6 = 1 / 42 = 0.0238
Answer:
h^-1(x) = (5x - 6)/2
Step-by-step explanation:
To find the inverse of h(x) = (2x + 6)/5, we need to solve for 'x':
y = (2x + 6)/5 ⇒ 5y = 2x + 6 ⇒ 5y - 6 = 2x ⇒ x = (5y - 6)/2
Therefore, h^-1(x) = (5x - 6)/2
Answer:
(5x-6)/2
Step-by-step explanation:
h(x) = (2x + 6)/5
y = (2x + 6)/5
To find the inverse, exchange x and y
x = (2y+6) /5
Then solve for y
Multiply each side by 5
5x = (2y+6)/5*5
5x = 2y+6
Subtract 6 from each side
5x-6 = 2y+6-6
5x-6 = 2y
Divide by 2
(5x-6)/2 = 2y/2
The inverse is
(5x-6)/2
Here, we are required to evaluate tan(sin^-1 (-4/5)).
tan(sin^-1 (-4/5)) = (-4/3)
Sin^-1 (-4/5) = θ
Therefore; ultimately Sin θ = (-4/5)
Since; Sine = opposite / hypothenus
Therefore, adj = √(5²) - (4²)
adj = 3.
However, since tan(sin^-1 (-4/5)) = tan θ
Therefore, tan θ = 4/3
However, since sin θ and tan θ are only negative in the fourth quarter;
Therefore, tan θ = (-4/3)
Read more:
First simplify the right side by combining like terms.
Since both terms contain an x, you can add them together.
So x + 5x simplifies to 6x.
So our equation now reads 2(x - 8) = 6x.
Solving from here, distribute the 2 through the
parentheses on the left side of the equation.
2(x) is 2x and 2(-8) is -16.
So we have 2x - 16 = 6x.
Now move the 2x to the right side by subtracting 2x from both sides.
This gives us -16 = 4x.
Now just divide both sides by 4 to get -4 = x.
Answer:
x = -4
Step-by-step explanation:
To find the value of x that makes a certain equation true means to solve the equation. You do this by rearranging the equation to make x the subject.
So,
2(x-8) = x+5x
2x - 16 = 6x
-16 = 6x-2x
4x = -16
x = -4
Hope this helps.